Using a cohesive zone modeling to predict the compressive and tensile behavior on the failure load of single lap bonded joint - Benamar Badr; Mokhtari Mohamed; Madani Kouider; Benzaama Habib (Fracture and Structural Integrity)
The aim of this work is to analyze the failure behavior of a simple lap joint of type metal / metal consisting of 2024-T3 Aluminum plate bonded with an Araldite adhesive using the finite element method to predict damage of the metal in tensile and compressive load under the effect of geometric parameters such as the length of the overlap and the geometric shape of the two plates according to the overlap length. The numerical analysis is performed by the ABAQUS calculation code. The adhesive was modeled by an element of the CZM cohesive zone. the adhesive will be submitted in mixed mode given the non-linearity of the two applied load. the calculation of the failure load will be determined according to the different parameters mentioned above. It is well demonstrated that the type of loading and the parameters taken into consideration condition the strength of the structure. The effect of these different parameters on the strength of the adhesive joint is presented as results by failure load curves